THE IMAGE OF INVESTMENT AND FINANCIAL SERVICES COMPANIES IN WWW LANDSCAPE (WORLD WIDE WEB) - Iancu Ioana Ancuta (Annals of the University of Oradea: Economic Science, 2011)
In a world where the internet and its image are becoming more and more important, this study is about the importance of Investment and Financial Services Companies web sites. Market competition, creates the need of studies, focused on assessing and analyzing the websites of companies who are active in this sector. Our study wants to respond at several questions related to Romanian Investment and Financial Services Companies web sites through four dimensions: content, layout, handling and interactivity. Which web sites are best and from what point of view? Where should financial services companies direct their investments to differentiate themselves and their sites? In fact we want to rank the 58 Investment and Financial Services Companies web sites based on 127 criteria. There are numerous methods for evaluating web pages. The evaluation methods are similar from the structural point of view and the most popular are: Serqual, Sitequal, Webqual / Equal EtailQ, Ewam, e-Serqual, WebQEM (Badulescu, 2008:58). In the paper: "Assessment of Romanian Banks E-Image: A Marketing Perspective" (Catana, Catana and Constantinescu, 2006: 4) the authors point out that there are at least four complex variables: accessibility, functionality, performance and usability. Each of these can be decomposed into simple ones. We used the same method, and we examined from the utility point of view, 58 web sites of Investment and Financial Services Companies based on 127 criteria following a procedure developed by Institut fur ProfNet Internet Marketing, Munster (Germany). The data collection period was 1-30 September 2010. The results show that there are very large differences between corporate sites; their creators are concentrating on the information required by law and aesthetics, neglecting other aspects as communication and online service. In the future we want to extend this study at international level, by applying the same methods of research in 5 countries from European Union: Germany, France, Britain, Italy and Spain.